Global species richness of hydrobiid snails determined by climate and evolutionary history. (29th June 2018) - Miller, Jonathan P.; Ramos, Marian A.; Hauffe, Torsten; Delicado, Diana
Abstract: Efforts to describe spatial patterns of freshwater diversity and to evaluate their underlying factors have traditionally been focused on some animal groups (e.g. amphibians, fish or dragonflies). Despite being a dominant component in continental aquatic ecosystems and crucial for determining priority areas for conservation, broad‐scale data on gastropod total species, endemic and threatened species richness are limited. Based on these biodiversity indices, we identify global hotspots, extinction risk along the elevational gradient and the drivers of species richness patterns in the largest group of freshwater gastropods, the family Hydrobiidae. Given the strong dependency to a nonmarine aquatic environment, the observed richness patterns of extant hydrobiid species could be significantly influenced by large‐scale geography and dispersal processes as well as climatic conditions affecting continental ecosystems. Therefore, we tested several predictions for species richness derived from ecological and evolutionary hypotheses postulated for other freshwater groups. Based on a comprehensive literature and biodiversity database review, we compiled the number of total, endemic and threatened species per freshwater ecoregion. We classified ecoregions as hotspots if each biodiversity index was in the top 25% of its range and assessed the effect of 13 environmental and evolutionary factors on species richness using generalised linear models. We identified 906 species and 157 genera of Hydrobiidae showing mainly a Nearctic–Palearctic distribution and 19 biodiversity hotspots, most located across the Mediterranean Basin. In our data set, 83% of the species were endemic to a single ecoregion. Of the 43% non‐data deficient species, we found almost three times more threatened than non‐threatened species, and extinction risk peaked at 1, 500 m a.s.l. Species richness was unequally distributed over biogeographic realms, increased with higher connectivity among ecoregions, and was negatively related with annual temperature range. Latitude and precipitation seasonality explained part of the richness variation by a nonlinear relationship. The identified hotspots correspond with those of other freshwater taxa. The hump‐shaped relationship of extinction risk with elevation is likely the consequence of decreasing natural and anthropogenic perturbations at higher elevations. Global hotspots of Hydrobiidae richness represent areas of climatic stability with medium precipitation and temperature seasonality that are well connected with other hydrological basins. Our results illustrate that both evolutionary and environmental factors determine these global patterns and that future changes of the latter factors may affect hydrobiid richness.